Analisis Aspek Quality of Service terhadap Peningkatan Kinerja Jaringan Gedung Kampus Universitas Dian Nusantara: Studi Kasus Lantai 4 Gedung Kampus Undira Tanjung Duren - Maulana, Arin; Purnama, Giri (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the impact of implementing Quality of Service (QoS) on improving wireless network performance on the 4th floor of the Dian Nusantara University Campus. The main issues identified include low throughput, high delay, unstable jitter, and poor internet connectivity during peak hours. The research employed an Action Research approach involving diagnosis, planning, implementation, evaluation, and learning stages. The solutions applied include bandwidth management using Simple Queue and Per Connection Queue (PCQ), network segmentation using VLAN, and real-time monitoring via The Dude application. Evaluation results show a significant improvement in network performance, with throughput increasing to 784.07 kbps, delay decreasing to 0.88 ms, and jitter stabilizing at 0.51 ms, while packet loss remained at 0%. The study concludes that the implementation of QoS with proper bandwidth configuration and network segmentation can effectively enhance network service efficiency and quality in an academic environment.